2012
DOI: 10.1021/om300485w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the MeReO3-Catalyzed Deoxygenation of Epoxides

Abstract: The reaction mechanisms for the MTO-catalyzed deoxygenation of epoxides and diols were investigated with the aid of density functional theory (DFT) calculations. The DFT results indicate that the reaction starts with a [2σ+2π] addition of epoxide to MTO to give a five-membered-ring rhena-2,5-dioxolane intermediate, followed by H2 addition, proton transfer, and extrusion of olefin to regenerate the catalyst. The experimental observation for formation and subsequent disappearance of diol appearing in the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 79 publications
3
27
0
1
Order By: Relevance
“…[11] These experimental observations are in accordance with the rate-determining step involving the cycloreversion of the diolate intermediate at elevated temperatures, which was studied by Gable and co-workers [17] and in recent independent density functional theory (DFT) calculations by Bi et al, Qu et al, and Liu et al. [25] Following these optimisation studies, the substrate scope was investigated by using a variety of vicinal diols under optimised reaction conditions, that is, 1.1 equiv. PPh 3 , chlorobenzene, 135 8C (Table 4).…”
Section: Resultssupporting
confidence: 85%
“…[11] These experimental observations are in accordance with the rate-determining step involving the cycloreversion of the diolate intermediate at elevated temperatures, which was studied by Gable and co-workers [17] and in recent independent density functional theory (DFT) calculations by Bi et al, Qu et al, and Liu et al. [25] Following these optimisation studies, the substrate scope was investigated by using a variety of vicinal diols under optimised reaction conditions, that is, 1.1 equiv. PPh 3 , chlorobenzene, 135 8C (Table 4).…”
Section: Resultssupporting
confidence: 85%
“…[24] After the publication of the Cook and Andrews paper, no new contributions to the rhenium-catalyzed DODH of diols were made until 2009, where Abu-Omar and co-workers showed that CH 3 ReO 3 catalyzed the H 2 -driven transformation of vicinal diols (and epoxides) into the corresponding alkenes (Table 1, entry 2). Abu-Omar and co-workers initially proposed that the reduction occurred before the condensation (thus favoring the right-hand side of Scheme 8), but a subsequent DFT study of the reaction by Lin and co-workers [58] revealed that the energy for the reduction of CH 3 ReO 3 to CH 3 ReO 2 by H 2 was significantly higher than for the reduction of the rhenium(VII) diolate to the corresponding rhenium(V) diolate (182 vs. 128 kJ mol À1 ), and it was therefore concluded that the pathway shown in the left-hand side of Scheme 8 was indeed the correct one. In addition, the method was not directly applicable to biomass-derived polyols like erythritol that decomposed under the reaction conditions.…”
Section: The Catalytic Dodh Reactionmentioning
confidence: 99%
“…This conclusion is supported by the direct observation of a catalytically inactive species as well as DFT calculations of the IR spectra of the relevant compounds. go condensation to a rhenium(VII) diolate that is subsequently reduced to a rhenium(V) diolate, has been suggested in computational studies by Lin and co-workers, [12] who investigated the CH 3 ReO 3 -catalyzed DODH of 1-phenyl-1,2-ethanediol using hydrogen as the reductant. The pathway shown on the righthand side of Scheme 2, in which CH 3 ReO 3 is reduced to CH 3 ReO 2 that subsequently undergoes condensation with the diol to a rhenium(V) diolate, has been suggested by Shiramizu and Toste [11] who concluded that methyldioxorhenium(V) is the catalytically relevant species.…”
Section: Introductionmentioning
confidence: 96%
“…The mechanism of DODH has been the subject of a number of studies, both experimental [10,11,17] and computational, [12,14,15] but the conclusions are conflicting, which in part may be because of the use of different catalysts and reductants. There is agreement on the existence of three stages in the reaction: condensation of the diol and the Re center, reduction of the Re center, and extrusion of the alkene accompanied by oxidation of the Re center, but the two main points of dispute are 1) the sequence of the condensation and reduction and 2) the identification of the rate-limiting step.…”
Section: Introductionmentioning
confidence: 99%